PERTUMBUHAN EKONOMI DAN PENDAPATAN ASLI DAERAH: STUDI EMPIRIS ATAS KORELASI RESIPROKAL - Agus Sunarya Sulaeman; Hasna Imtiyaz Hanifah (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2022)
This study aims to analyze the reciprocal effect between economic growth and local own-source revenue. The research scope of this study is based on Java—Bali region in 2015—2019. Using purposive sampling, the data used in this research is taken from the DJPK and BPS websites. The method of this study is analyzed with the two-stage least square (2SLS) panel data regression method with cross-section random effect model as well as white-cross section covariance coefficient in the GDRP equation and period weights (PCSE) in the LOR equation. This research managed to prove the significant positive reciprocal effect between economic growth and LOR. Other factors related such as General Allocation Fund, Revenue Sharing Fund, and HDI in the GDRP equation also have a significant positive influence on economic growth. Meanwhile, labor, local taxes, and local retributions variables also own similar results on LOR. However, Special Allocation Fund and population has significant negative effect on economic growth and LOR, respectively. Moreover, capital expenditure with a lag of two years shows a negative and insignificant effect on economic growth.